The concepts of center and periphery in Enrique Dussel's transmodern project - Natteri Romero, Iván (2016)
Enrique Dussel transmodern project tries to form a new perspective on the most critical and novel political ethics of our times. But in spite of its articulation with metaphysics, it does so with geopolitics. In this last one tend to carve as central nucleus of the argumentation the socio-political categories of center and periphery. Without them, one could not speak of Modernity, nor of its overcoming; the transmodernidad. This research attempts to account for this intrinsic categorial inclusion in Dussel convivial project. Space will also be explored as a way of justifying the center periphery.